La construcción del conocimiento en la primera infancia / The construction of the knowledge in the first infancy - Villarroel Dávila, Paola (2012)
Current times demand to discover and rediscover the ways of building knowledge in the different developmental stages of their importance in the management, understanding and ownership of the objective and subjective reality of the human being. The issue deserves to start at the beginning, that is when the child is born and begins the adventure of learning through their senses, movements, interactions, so this paper presents main ideas on cognitive development in early childhood and factors involved in a systemic mink. The theoretical contributions of Piaget, Vygotsky and Bruner are leading the way in identifying internal and external aspects interconnected to the progress of intellectual abilities such as language, reasoning, the scenario approach, the construction of concepts... that will shape the symbolic and mathematical thinking. This process was developed from movements and actions that lead to the discovery of self, the natural world, cultural and, later, to the formation of symbolic structures to interpret and give meaning to individual and group learning. Affectivity is a key element in this evolutionary stage or limited power because of cognitive, motor and also ensures holistic development. So, too, education plays a key role in the operation of the school family and they are the first agents of socialization that must obey the principles of integrity, creativity and significance to form happy children with opportunities to feel, think and do.